If it's not what You are looking for type in the equation solver your own equation and let us solve it.
52=4x+2(x+8)
We move all terms to the left:
52-(4x+2(x+8))=0
We calculate terms in parentheses: -(4x+2(x+8)), so:We get rid of parentheses
4x+2(x+8)
We multiply parentheses
4x+2x+16
We add all the numbers together, and all the variables
6x+16
Back to the equation:
-(6x+16)
-6x-16+52=0
We add all the numbers together, and all the variables
-6x+36=0
We move all terms containing x to the left, all other terms to the right
-6x=-36
x=-36/-6
x=+6
| (-5x)-3=9 | | 3m+10-30=15m-6 | | -8=-10+d/2 | | -54=6(1+w) | | -7(6+t)-1=20 | | -5x-(3)=9 | | -66=-8z+2z | | 3p-5=2(4p-20) | | 6=-2(7-e) | | 44=-2w-2w | | 5x•=x | | -4(d-12)=40 | | 45+2e=12-e | | 52=4+3(2x+10) | | 8a+20=4(2a+5) | | 2=p+11/4 | | 4x-2x+2x-3x=9+6 | | 2g+18=3(2g-6) | | -17.32=-1.6+4.4r+3.2 | | 400+x=6800 | | -15=-9d-6d | | 8y-13y-2=15 | | 5(2x+3)-5=40 | | 4/5=m/4 | | 5(p+3)+1=-29 | | 24=10y+2y | | -4(3v+7)-3v=-133 | | 3(2x-3)-2(1-3x)=61 | | 7=1+3w | | 2x+10+4x-2=140 | | -12x-7=18 | | 3^2b+6+1*2b=15+2b |